Complete starter guide to bonsai : growing from seed or seedling--wiring, pruning, care, and display - Squire, David, 1938- (Creative Homeowner, 2024)
Creating bonsai, an ancient art form that encourages meditation and contemplation, can be an intimidating art to start because of its intricate and precise nature. Starting with the definition of what a real bonsai is, the author discusses the spirit and aesthetics of creating bonsai then continues with the materials needed, how to prune, pinch, water, feed and display your piece.